Studying The Health Implications of Metro Rail Or Highway ‎Construction on Local Communities - V. S. , Prof Dr. Gigimon; Lee , Parvathy Anu (International Journal of Basic and Applied Sciences, 2025)
This paper examines the frequently neglected public health consequences of constructing metro rail and highways on adjacent villages, considering Indian law. As India’s cities grow quickly and its economy grows, infrastructure development is speeding up. This is bad for the ‎health of people living near construction sites. Air pollution, noise pollution, contaminated water, and the stress of having to move your ‎whole life are all possible risks. For instance, the Center for Science and Environment (2019) says that since PM2.5, there have been more ‎instances of asthma and bronchitis in the affected communities. Five levels at construction sites for the Delhi Metro were three to five times ‎higher than what the World Health Organization says is safe. ‎ ‎ But the current rules in India don’t do enough to deal with the health problems that come with these kinds of big city projects, even though ‎they do have these effects.‎ The analysis includes a thorough look at Indian laws, pertinent case law, and environmental rules. It also compares the legal systems of ‎other countries, such as the US, the EU, Australia, and Canada. These countries use health impact assessments (HIAs), public involvement ‎methods, and strict monitoring systems to plan infrastructure. ‎ The results show that the Indian court system generally puts economic or environmental issues ahead of health concerns, rather than community health. Health impact assessments are not actually a part of the process of managing infrastructure. There have been no systemic ‎legal protections or enforceable health standards put in place for infrastructure projects, even though the courts play a big role in establishing ‎the right to health under Article 21. ‎ This study highlights the importance of health impact assessments (HIAs), public involvement, and post-approval monitoring in ensuring ‎proper accountability for health outcomes. This article highlights the imperative necessity for reform by juxtaposing India’s policies and ‎regulations with those of other developed countries. It calls for health impact assessments to be a required part of environmental impact ‎assessments (EIAs), more community participation, and health audits after projects. Health departments, urban planners, and legal bodies ‎should work together, it says, to institutionalize development that is more holistic and preventative. ‎ Rather than relying on reactive legal frameworks, the report argues for proactive frameworks that address health concerns at every stage of ‎infrastructure development. Public health must be recognized as an essential ethical and legal issue if India’s urban development is to be ‎inclusive, sustainable, and socially equal. Detailed legal and policy recommendations are offered in the paper to align the administration of ‎India’s infrastructure with the country’s constitutional guarantee of the right to health‎.